Pengaruh Citra Merek dan Kualitas Produk Terhadap Keputusan Pembelian Mi Instan Merek Indomie (Studi Kasus Pada Mahasiswa/i Universitas Bhayangkara Jakarta Raya) - Damayanti, Vina; Thamrin, Djuni (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
In this case, the research conducted aims to determine the influence of brand image and product quality on purchasing decisions for Indomie brand instant noodles among students at Bhayangkara University, Jakarta Raya as consumers. This research uses a quantitative type of research where the objects used are students who have bought Indomie brand instant noodle shoes. The data source for this research comes from primary data. The sampling method for this research used the Lemeshow formula with the number of samples used in this research being 100 respondents. The hypothesis testing data analysis method in this research was processed using Structural Equation Modeling (SEM) with the SmartPLS 4.1 application. The results of data processing show that brand image and product quality simultaneously (together) have a positive and significant effect on purchasing decisions. With all the limitations of only conducting research on students at Bhayangkara University, Jakarta Raya, Management Study Program Class of 2020, this can provide benefits and suggestions for further research. In this research, it reflects the variables of brand image and product quality on purchasing decisions in one research model.